2021
DOI: 10.1016/j.heliyon.2021.e07915
|View full text |Cite
|
Sign up to set email alerts
|

Spatial interaction between breast cancer and environmental pollution in the Monterrey Metropolitan Area

Abstract: This research examines the spatial structure of a sample of breast cancer (BC) cases and their spatial interaction with contaminated areas in the Monterrey Metropolitan Area (MMA). By applying spatial statistical techniques that treat the space as a continuum, degrees of spatial concentration were determined for the different study groups, highlighting their concentration pattern. The results indicate that 65 percent of the BC sample had exposure to more than 56 points of PM 10 . Likewise, spatial clusters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
3
0
3
Order By: Relevance
“…Among cancer types, breast cancer is the most common cancer found in women and causes their deaths [ 2 ]. Many studies have revealed that breast cancer is caused by environmental factors, such as obesity [ 3 ], heavy smoking [ 4 ], and genetic factors such as breast cancer gene ( BRCA) 1 , BRCA2 , phosphatase and tensin homolog ( PTEN ), tumor protein P53 ( TP53 ), cadherin 1 ( CDH1 ), and serine/threonine kinase 11 ( STK11 ) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among cancer types, breast cancer is the most common cancer found in women and causes their deaths [ 2 ]. Many studies have revealed that breast cancer is caused by environmental factors, such as obesity [ 3 ], heavy smoking [ 4 ], and genetic factors such as breast cancer gene ( BRCA) 1 , BRCA2 , phosphatase and tensin homolog ( PTEN ), tumor protein P53 ( TP53 ), cadherin 1 ( CDH1 ), and serine/threonine kinase 11 ( STK11 ) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, los estudios poblacionales que han evaluado la asociación entre la exposición a la contaminación del aire y el cáncer de mama no han sido consistentes [44]. Si bien se han encontrado asociaciones fuertes con óxidos de nitrógeno (NO x ) y dióxido de nitrógeno (NO 2 ) [11,14], especialmente con cáncer de mama ER(+)/PR(+) [45], en el caso del PM, los hallazgos de estudios epidemiológicos recientes son muy variables, encontrándose relaciones fuertes [13], moderadas o débiles; incluso algunos estudios han sugerido que la exposición a PM puede aumentar la mortalidad pero no la morbilidad por esta patología [21].…”
Section: Discussionunclassified
“…Algunos estudios epidemiológicos han reportado hallazgos estadísticamente significativos, que señalan una relación entre la exposición a contaminantes del aire y la incidencia de cáncer de mama [8,[11][12][13]. En la mezcla de contaminantes en el aire confluyen compuestos como hidrocarburos aromáticos policíclicos (HAP) y metales que pueden actuar como cancerígenos o disruptores endocrinos [14].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…PM2.5, NO2, and traffic-related emissions may act as mammary carcinogens [ 15 , 82 ]. A study in Mexico found significant geospatial clustering of BC cases near pollution sources including refineries and industrial facilities [ 83 ]. However, the associations with PM are complex; specific components like nickel and vanadium, rather than overall PM levels, may drive the increased risk [ 73 – 75 ].…”
Section: Discussionmentioning
confidence: 99%